Perkawinan Beda Agama - Zainal Arifin (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2018)
Marriage aims to foster family sakinah mawaddah and rahmah. In an effort to realize this goal, Islam offers harmony between couples, which is commensurate with both the social strata or the same beliefs. The occurrence of interfaith marriages is considered contrary to the purpose of marriage, how can it be able to create a family that is sakinah, mawaddah, and mercy . In the perspective of sadd az-zari'ah, interfaith marriage is prohibited because it is feared that it can damage the existence of one's faith. The Indonesian Ulema Council, the Muhammadiyah PP Majlis, and the NU cleric banned interfaith marriages on the basis of closing the potential consequences of interfaith marriages. This ban also gained momentum when it was linked to the discourse of Christianization that is rife today. Interfaith marriages today are not in accordance with the purpose of inter-religious marriage at the time of the Prophet Muhammad, now inter-religious marriage is only a proof of prestige and satisfaction of mere lust not for the glory of Islam so that it is better avoided.